Does psychological well‐being mediate the association between experiences of acts of offensive behaviour and turnover among care workers? A longitudinal analysis. (17th August 2012) - Clausen, Thomas; Hogh, Annie; Carneiro, Isabella Gomes; Borg, Vilhelm
Abstract Aim To investigate whether the psychological well‐being of care workers in the Danish eldercare services mediated the association between experiences of acts of offensive behaviour and actual turnover. Background Research suggests that experiences of acts of offensive behaviour are associated with risk of turnover. However, little is known about the longitudinal associations between experiences of different types of offensive behaviour (threats, violence, bullying, and unwanted sexual attention) and risk of actual turnover. Design A prospective cohort study. Methods The study was conducted among employees in the eldercare services in Denmark. Employees aged 55 or more and non‐care staff were excluded from the study. Employees who were working in eldercare at baseline (2005) and no longer worked in eldercare at follow‐up (2006) were interviewed through questionnaires. Respondents to this questionnaire were coded as cases of turnover (N = 608) and were compared with employees who had not changed jobs during follow‐up (N = 4330). Data on experiences of acts of offensive behaviour and well‐being were measured at baseline. Data were analysed using logistic regression analysis. Results Frequent and occasional experiences of bullying and threats and occasional experiences of unwanted sexual attention at baseline entailed a significantly increased risk of turnover at follow‐up. Further analyses showed that psychological well‐being significantly reduced the risk of turnover and that well‐being partially mediated the association between bullying and turnover and fully mediated the association between threats, unwanted sexual attention, and turnover. Conclusion Prevention of threats, unwanted sexual attention and – especially – bullying may contribute towards improving well‐being and reducing turnover among eldercare staff.